Poly(thionine)-modified screen-printed electrodes for CA 19-9 detection and its properties in Raman spectroscopy - Castaño-Guerrero, Yuselis (2022)
Polythionine (PTH) is an electroactive compound known for its excellent electron transfer capacity. It has stable and redox centers in its structure, and it can also be generated by electropolymerization of thionine (TH). Due to its properties, it has been used in a large number of applications, including the construction of electrochemical biosensors. In this work, PTH is explored for its ability to generate electrons, which allows it to act as an electrochemical probe in a biosensor that detects CA 19-9 on two different substrates, carbon and gold, using differential pulse voltammetry (DPV) as a reading technique in phosphate buffer (PhB). The analytical features of the resulting electrodes are given, showing linear ranges from 0.010 to 10 U/mL. The Raman spectra of PTH films on gold (substrates or nanostars) and carbon (substrates) are also presented and discussed as a potential use for SERS readings as complementary information to electrochemical data.